Strategi Pengembangan Koperasi dengan Analisis SWOT (Studi Kasus di KSU Maju Jaya) - Sir Kalifatullah Ermaya (Ekonomi dan Bisnis, 2019)
The digital era 4.0 is currently making the environment turbulent. Economic actors tend to be faced with intense competition. One of these economic actors is the Koperasi Serba Usaha (KSU) Maju Jaya, Kuningan. Every aspect in the cooperative is an important thing that must be understood so that it can be developed and utilized properly. At present, KSU Maju Jaya, Kuningan will develop its business. Therefore, KSU Maju Jaya, Kuningan needs to look at the conditions that occur, both internally and externally so that it can make an appropriate decision in developing its business. The researcher used SWOT analysis to determine the position of the business competition. The results of this analysis showed that KSU Maju Jaya, Kuningan is in Quadrant III with x axis = -0.32 and y axis = -0.25. Hence, some strategies that must be carried out by KSU Maju Jaya, Kuningan are Concentration Strategies, Product and Market Development Strategies and Innovation Strategies.